MIGRATION IN THE MOUNTAINOUS REGIONS OF EURASIA: PAST AND PRESENT (Tajikistan, Kyrgyzstan, Afghanistan,and Pakistan) - OLIMOVA, Saodat (CENTRAL ASIA AND THE CAUCASUS, 2005)
Pamiro-Alai, Tien Shan, Hindukush, Karakorum, and the Himalayas are not only the highest mountain systems on Earth located in the heart of Eurasia, they are also the place of residence of Kyrgyz, Tajiks, Pashtuns, Punjabis, the peoples of Badakhshan, Chitral, Gilgit, Nuris-tan, and Punjab, etc. Mountains occupy 93% of Tajikistan, 94% of Kyrgyzstan, 61% of Pakistan, where 25% of the country’s population lives, and 60% of Afghanistan (occupied by 89% of the population).1 The inaccessibility, isolation, and remoteness of these regions have helped to retain the ancient traditions and exclusively cultural, linguistic, and anthropological diversity of the local population. These factors and the harsh bio-climatic conditions make the mountain dwellers extremely vulnerable. Nevertheless, in recent decades the outside contemporary world has been encroaching more and more on them, and they are feeling its impact. Political upheavals, the disintegration of the U.S.S.R. and formation of new states in Central Asia, the war in Afghanistan, the antiterrorist campaign, Indo-Pakistani relations, and the Kashmir problem have all had a direct influence on the residents of this part of the world. Their isolation is gradually being broken down by such globalization processes as mobility of the population, development of infrastructure, evolution of information technology, and so on. One of the most noticeable new phenomena in the life of the mountain dwellers is large-scale migration. Leaving the mountains in search of a living, which has been an inviolable part of the activity of mountain dwellers from time immemorial, has now acquired top priority for many regions of Central Asia, Afghanistan, and Pakistan. Its dimensions can be judged by the number of people participating in this process: 350,000-500,000 people in Kyrgyzstan, 650,000 in Tajikistan,1,500,000-1,700,000 in Afghanistan, and 4-5 million in Pakistan. Revenue from labor migration is playing an increasingly important role in the development of these states. For example, in 2004, according to estimates, labor migration brought 500 million dollars into Tajikistan, more than 120 million dollars into Kyrgyzstan, approximately 200 million dollars into Afghanistan, and 3.5 billion dollars into Pakistan. Along with the increase in volume of labor migration, its quality, areas, types, and even the forms of economic, social, and cultural influence on the life of the mountain communities have also changed. The urgency of this problem is giving rise to discussions in which opposing views are being ex-pressed about whether labor migration is helping or interfering with the development of these regions. Our article is devoted to issues relating to labor emigration of mountain dwellers and its economic and social influence on the life of the mountain communities in Kyrgyzstan, Tajikistan, Afghanistan, and Pakistan. The article was prepared using data from the Migrants from Badakhshan2 and External Labor Migration in the Kyrgyz Republic (2003)3 studies, work on labor migration in Tajikistan carried out by the Sharq Center in 2002-2004, as well as a series of interviews conducted by the present author and Professor Muzaffar Olimov in March-June 2004 in Tajikistan, Kyrgyzstan, Kazakhstan, Russia, Afghanistan, and Pakistan under the IOM (International Organization for Migration)program.